Synergistic effect of nano-silica, steel slag, and waste glass on the microstructure, electrical resistivity, and strength of ultra-high-performance concrete - Mohammed Abbas J.; Hassan Maan S.; Al-Quraishi Hussein (Open Engineering)
This study examined the microstructure characteristics, electrical resistivity (ER), and mechanical properties of ultra-high-performance concrete (UHPC) made with nano-silica (NS), electric arc furnace slag (EAFS), and waste glass powder (WGP). Eight concrete mixtures of binary and ternary blends were assessed to investigate the possible relationships between the observed physical and microstructural features with the obtained compressive and flexural strengths. The individual and combined effects of NS, EAFS (up to 50% replacement of silica sand), and WGP (up to 30% cement replacement) on the examined properties were evaluated. Scanning electron microscopy (SEM), thermogravimetric (TG) analysis, X-ray diffraction (XRD), ER, and pH values, and measurements were employed. SEM examination indicated that using NS along with EAFS and WGP reduced gap space around the fiber, and the enormous single cracks turned into numerous small cracks, thereby improving bonding and flexural strength. TG and XRD studies supported this finding. The ER for the EAFS specimens was enhanced without compromising the alkalinity range of concrete, as proved by pH tests, which address the possible corrosion problem of reinforcement. Thus, sustainable UHPC is achievable.